(untitled) (Asian Journal of Medical and Biological Research, 2021)
Bakanae disease has been reported from almost all the rice growing countries in the world. The disease has been emerged as a major problem in some of the Asian countries including Bangladesh. Bakanae is becoming a serious threat to sustainable rice production in Bangladesh particularly in the northeastern part of the country and accounted for causing up to 25% yield losses. The disease has become difficult to manage due to lacking appropriate disease diagnosis. Fusarium fujikuroi mainly caused this disease but other Fusarium species are also reported to be involved for causing this disease. It, therefore, is crucial to understand the association of Fusarium species with Bakanae disease for sustainable rice disease management in Bangladesh. Asian J. Med. Biol. Res. December 2020, 6(4): 608-610